Decision making in a complex world: Using OPTamos in a multi-criteria process for land management in the Cuitzmala watershed in Mexico. (September 2017) - Grima, Nelson; Singh, Simron J.; Smetschka, Barbara
Highlights: A land management decision process was conducted in the Cuitzmala watershed (Mexico). An iterative transdisciplinary research approach was applied. Qualitative and quantitative data was generated in the process. The data was handled with the new software OPTamos. The results from OPTamos provided impetus to stakeholder discussions and agreement on next steps. Abstract: Payments for Ecosystem Services (PES) are incentives offered to land owners or managers in exchange for practices that benefit society with ecological goods and/or services. For the success of PES schemes, the involvement of stakeholders, their needs, knowledge, and perspectives has been found beneficial. This paper presents a new approach in engaging stakeholders based on an iterative transdisciplinary framework for a Social Multi-Criteria Evaluation (SMCE) decision-making process. After a comprehensive review of existing options, the paper describes the development and application of a new software, OPTamos, to allow for efficient handling and processing of large volumes of quantitative and qualitative data generated from stakeholder workshops. Applied to a land use related decision in the Cuitzmala watershed, in the state of Jalisco in Mexico, the outcomes from this approach resulted in acceptable land management options for the entire area of the watershed that satisfied criteria generated by the stakeholders themselves and to finally develop an action plan.